A Glimpse into the History of The Benteng Heritage Museum: The Heirloom of Chinese Peranakan Amidst the Old Market of Tangerang City - Ribawati, Eko (History Education, University of Jember, 2024)
The Benteng Heritage Museum is a Chinese Peranakan Museum located in Tangerang City. This museum holds various collections of Chinese cultural relics. The purpose of this study was to determine the development of the Heritage Fort Museum. The research method is the historical method which consists of heuristics, criticism, interpretation, and historiography. The results showed that the Benteng Heritage Museum was inaugurated in 2011. The museum has received collections from various groups, from collectors of rare objects to observers of Chinese history and culture.